Implementasi Metode PID dalam Sistem Kendali Temperatur Pada Ruang Produksi “Clean Room” Berbasis IOT - Rifky Adji Fadlani (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
A clean room is a clean room free from dust and air which can affect product quality. Factors that influence product quality are temperature, humidity and air particles. The condition of the cleanroom cannot be guaranteed to be clean and sterile at all times without a control system. Therefore, a tool was developed that can monitor, control and provide warnings if the room is not in suitable condition. In this research, the PID method was used using the split range control method to control temperature and particles to help optimize the temperature and particle control process. SHT30 sensor for temperature and humidity detection. PMS5003 sensor for air particle detection. The results of sensor detection can be monitored on the website and LCD. The output from the control system will regulate the speed of the blower motor, regulate the temperature and turn on fogging to reduce particles in the air. So the PID method with the split range control method is used as an appropriate temperature control system, so that the temperature and air particles remain in a stable condition. The results of the humidity percentage error are 1.43% and the temperature error is 1.14%, PMS5003 produces errors for particles with a size of 0.1, namely 2.3%, 0.5, namely 5.3%, 1, namely 4.2%, and 5 which is 4%. The PID control system takes approximately 885 seconds to reach 100% setpoint.